A cradle to cradle approach towards remediation of uranium from water using carbonized arecanut husk fiber. Issue 7 (1st February 2023) - Dhanya, V.; Rajesh, N.
Abstract : Sustainable materials for remediation of pollutants from water is the need of the hour. Abstract : Sustainable materials for remediation of pollutants from water is the need of the hour. In this study two carbonaceous adsorbents prepared through hydrothermal carbonisation and pyrolysis from arecanut husk fiber, an agricultural waste material were used for the adsorption of uranium from water. Batch adsorption data as interpreted using the Langmuir model showed adsorption capacities of 250 mg g −1 and 200 mg g −1 respectively at pH 6 for the hydrochar (AHFC) and the pyrochar (AHFT) exceeding that reported for most of the unmodified biochars. The adsorption followed pseudo-second order kinetics and was exothermic in nature. The high selectivity and excellent removal efficiencies on application to environmental ground water samples and good regeneration capacity make these sorbents promising eco-friendly materials for uranium remediation from water.